Adsorption of SARS‐CoV‐2 Spike Protein S1 at Oxide Surfaces Studied by High‐Speed Atomic Force Microscopy. Issue 2 (5th February 2021) - Xin, Yang; Grundmeier, Guido; Keller, Adrian
Abstract : Biointerfaces The cover image shows the adsorption of SARS‐CoV‐2 at metal‐based fomite surfaces. The spike protein subunit S1 is the outermost point of the viral envelope and thus mediates the initial contact between the virus and the fomite surface. High‐speed atomic force microscopy movies reveal that S1 protein adsorption proceeds faster at TiO2 surfaces than at Al2 O3 surfaces. More details can be found in article number 2000024 by Adrian Keller and co‐workers